Protective effects of beta glucan in brain tissues of post-menopausal rats: a histochemical and ultra-structural study. (3rd March 2016) - Selli, Jale; Unal, Deniz; Mercantepe, Filiz; Akaras, Nurhan; Kabayel, Rabia; Unal, Bunyami; Atilay, Hilal
Abstract: Decline of estrogen during menopause has been associated with numerous significant changes that have been linked to many pathophysiological complications. In addition, ovarian hormone deficiency increases the production of reactive oxygen radicals which could result in oxidative stress and cell damage. While estrogen therapy is often considered to overcome the behavioral and physiological shortcomings, antioxidants are gaining popularity for their beneficial property. For this purpose, in the present study, utilizing the antioxidant properties of beta glucan has been examined in treatment of menopause induced oxidative stress in cerebral neurons. Four groups of female Wistar rats were used: control, ovariectomy, ovariectomy + estrogen treated and ovariectomy + beta glucan treated. We observed a significant increase in neural degeneration in ovariectomized rats as compared to controls. Moreover, increased oxidative stress in the brains of the ovariectomized rats has been detected by performing immunohistochemical analysis. A large number of immuno-positive cerebral neurons have been observed in ovariectomy group rat brains. Interestingly, providing beta glucan treatment to ovariectomized rats reduced the number of degenerated neurons. Our study is the first to examine light and electron microscopic examination and immunohistochemical and stereological analysis of estrogen depletion in rats and to test protective role of beta glucan in the experimental study.